2021
DOI: 10.3897/compcytogen.v15.i4.76761
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the banding sequence pool and new data on chromosomal polymorphism in natural populations of Chironomus agilis Shobanov et Djomin, 1988 (Diptera, Chironomidae)

Abstract: Quantitative and qualitative analysis of chromosomal polymorphism in 19 natural populations of Ch. agilis had been performed. Most studied populations showed a medium level of chromosomal polymorphism: on average 45±3.0% of specimens are heterozygotes with 0.52±0.01 heterozygotic inversion per larvae. Besides inversions, B-chromosomes were found in two populations. The total number of banding sequences found in banding sequence pool of Ch. agilis is 16. Three banding sequences – p’agiB3, p’agiD3, p’agiF3 – are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…2 ) Previously, p’ag2C1 was considered to be unique to the species, but recent data on chromosomal polymorphism of Ch. agilis ( Golygina and Ermolaeva 2021 ) have shown that a banding sequence identical to p’ag2C1 does exist in the banding sequence pool of Ch. agilis (p’agiC2), although up to now it has been found only once.…”
Section: Results and Discussionmentioning
confidence: 99%
“…2 ) Previously, p’ag2C1 was considered to be unique to the species, but recent data on chromosomal polymorphism of Ch. agilis ( Golygina and Ermolaeva 2021 ) have shown that a banding sequence identical to p’ag2C1 does exist in the banding sequence pool of Ch. agilis (p’agiC2), although up to now it has been found only once.…”
Section: Results and Discussionmentioning
confidence: 99%